Fluorescent sophorolipid molecular assembly and its magnetic nanoparticle loading: a pulsed laser process - Singh, Pradeep Kumar; Mukherji, Ruchira; Joshi-Navare, Kasturi; Banerjee, Abhik; Gokhale, Rohan; Nagane, Satyawan; Prabhune, Asmita; Ogale, Satishchandra (Green Chemistry, 2013)
We report realization of strong green fluorescence in a fully biocompatible highly spherical mesoscale molecular assembly of sophorolipid created by pulsed UV laser processing of a water-based dispersion of sophorolipid. Remarkably, the said fluorescence is totally absent in the original molecule of sophorolipid and is thus the property of the pulsed laser induced modifications in the molecule and the assembly. We have separately examined the consequences of laser irradiation for glucose and oleic acid components which form the sophorolipid. This fluorescence character appears to be driven by the oleic acid component while the assembly process is assisted by the glucose component. Importantly the laser synthesized mesostructures can be easily redispersed in an aqueous medium after being dried and can also be loaded with magnetic nanoparticles (magnetite) for inducing the hyperthermia effect.